Frontotemporal lobar degeneration with TDP‐43 proteinopathy and chromosome 9p repeat expansion in C9ORF72: clinicopathologic correlation. Issue 2 (18th June 2012) - Bigio, Eileen H.; Weintraub, Sandra; Rademakers, Rosa; Baker, Matt; Ahmadian, Saman S.; Rademaker, Alfred; Weitner, Bing Bing; Mao, Qinwen; Lee, Kyung‐Hwa; Mishra, Manjari; Ganti, Rakhee A.; Mesulam, M‐Marsel
<x xml:space="preserve">Abstract</x> Mutations in C9ORF72 resulting in expanded hexanucleotide repeats were recently reported to be the underlying genetic abnormality in chromosome 9p‐linked frontotemporal lobar degeneration with TAR DNA‐binding protein of 43 kD (TDP‐43) proteinopathy (FTLD‐TDP), amyotrophic lateral sclerosis (ALS), and frontotemporal lobar degeneration with motor neuron disease (FTLD‐MND). Several subsequent publications described the neuropathology as being similar to that of FTLD‐TDP and ALS without C9ORF72 mutations, except that cases with mutations have p62 and ubiquitin positive, TDP‐43 negative inclusions in cerebellum, hippocampus, neocortex, and basal ganglia. The identity of this protein is as yet unknown, and its significance is unclear. With the goal of potentially uncovering the significance of these inclusions, we compared the clinical, pathologic and genetic characteristics in cases with C9ORF72 mutations to those without. We confirmed the apparent specificity of p62 positive, TDP‐43 negative inclusions to cases with C9ORF72 mutations. In hippocampus, these inclusions correlated with hippocampal atrophy. No additional correlations were uncovered. However, this is the first report to show that although most cases with C9ORF72 mutations were TDP type B, some of the pathologic characteristics in these cases were more similar to TDP types A and C than to type B cases. These include greater cortical and hippocampal atrophy, greater ventricular dilatation, more neuronal loss and gliosis in temporal lobe and striatum, and TDP‐43 positive fine neuritic profiles in the hippocampus, implying that the C9ORF72 mutation modifies the pathologic phenotype of FTLD‐TDP type B.